La dissuasion nucléaire et les rapports sino-japonais - l'interaction entre une puissance nucléaire et une puissance non nucléaire en Asie de l'Est (Note) - Shihmin, Chen (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1997)
Since the end of 1950s, the Japanese nuclear policy has consisted in keeping the legal option open for the development of the "defensive" nuclear weapons and maintaining a nuclear potential. The motivation of this" open nuclear option" of Japan would be mainly the development of the nuclear force of China. The us retreat of all the ground-launched and submarine-launched tactical nuclear weapons in 1991 implied the end of the age of dependence on tactical nuclear weapons for "war-fighting" in Asia. The conventional deterrence would already be sufficient for maintaining the stability of the East Asia. The mission of the extended nuclear deterrence of the United States could be reduced to Us vital role for countering only the nuclear attack of other country, not for any conventional attack. The controversies about the "antimissile defense" have influenced the security relationship between China and Japan. The important strategic significance of the antimissile defense for Beijing would be that a strategy of the first strike against China would be easier to consider. A theater missile defense in Japan would be less challenging for China and would be useful against the threat of missiles from North Korea. Nonetheless, a strategic missile defense could have a destabilizing impact on Sino-Japanese security relations. The Japanese nuclear policy would be a hind of "recessive deterrence" which operates by the potential and the possibility of developing nuclear weapons. The nuclear crisis in Korea provides a chance to observe the working dynamic of this deterrence. Owing to the worry about the nuclear proliferation of Japan, Tokyo finds it appropriate to ask Beijing to prevent the nuclear development of the North Korea and to maintain the credibility of the extended deterrence of the United States.